Effect of bracing on respiratory mechanics in mild idiopathic scoliosis. Issue 7 (July 1989) - Kennedy, J D; Robertson, C F; Hudson, I; Phelan, P D
Abstract : The use of a corrective orthopaedic brace is an established form of management for patients with progressive idiopathic scoliosis. Thirteen patients with mild idiopathic scoliosis were studied with and without the corrective brace applied. Lung volumes and the pattern of chest wall and abdominal movement were measured during quiet breathing. Transdiaphragmatic pressures were measured in six of the patients and upper ribcage movement in seven patients. Application of the brace resulted in a significant reduction in vital capacity (14%), functional residual capacity (22%), and total lung capacity (12%). There was no effect on respiratory rate or minute volume. In the erect position the pattern of chest wall movement was altered with a reduction in lower ribcage movement of 46% and abdominal wall of 39% and an increase in upper ribcage movement of 43%. These changes were greater in the supine position. There was at least a twofold increase in end inspiratory and end expiratory gastric pressures during tidal breathing, but oesophageal pressures were not affected by the brace. Transdiaphragmatic pressures showed a similar twofold increase, which implies a substantial increase in the work of breathing. In view of the doubts concerning the influence of bracing on the natural history of idiopathic scoliosis and the substantial functional effect of bracing on the respiratory system, it is suggested that the current practice of bracing in this condition needs to be reviewed.